A study to assess the effectiveness of short training session on immunization knowledge of mothers attending immunization clinic - Agarwal, Anil Kumar; Swami, Piyush Datt; Dwivedi, Shatkratu (International Journal Of Community Medicine And Public Health, 2018)
Background: Parents knowledge about immunization is India’s primary tool against the menace of child not immunized completely. The parents especially mothers should have basic knowledge of immunization in under five children. Methods: The study evaluates knowledge and behaviour of mothers regarding the immunization of 250 infants who attended Immunization clinic of Madhav dispensary J.A. Hospital, Gwalior Madhya Pradesh by simple random sampling method under the PSBH project completed by MBBS Final Part I students. Results: Brief structured interview with transient training and structured questionnaire techniques were used to collect responses from the mothers. In total 59.32% mothers were aware about the immunization aspects and only 45.8% were about the mandatory vaccines had been rendering adequate knowledge and they were not much reflective of the same when being questioned on the knowledge parameter. The study revealed that out of 250 mothers, 40% were in the age group of 21-25 years. After immunization based brief transient training given to mothers, their knowledge about immunization aspects and individual vaccines under five children was significantly improved from pre test assessment mean score 118.1±59.3 to post test assessment 224.1±89.6 respectively. Conclusions: There are several loopholes in the mother’s knowledge regarding immunization. Many of them had no knowledge about compulsory vaccines. Despite inadequate knowledge and attitude of mothers towards infant immunization, the majority of mothers had good change (42.4%) and 32.3% due to seeking of information about practice of infant immunization and individual vaccine. From this point of view, it is possible to conclude that mothers’ immunization practice was not really based on their knowledge and attitude regarding immunization of infants. Maternal education and socio economic status were significantly associated with good knowledge.